Pendampingan Kegiatan Literasi sebagai Upaya Meningkatkan Minat Baca Pada Siswa Sekolah Menengah Pertama di Desa Bogares Lor Kecamatan Pangkah-Tegal - Destary Praptawati; Riana Permatasari; Afina Murtiningrum (Indonesian Journal of Community Services, 2023)
The Indonesian government has implemented the School Literacy Movement as a solution to the problem of low student interest in reading, but not all schools are able to implement the program. The pesantren-based school, Attin Al Khair Junior High School is one of the private Junior High Schools in Pangkah Sub-districts, Tegal, which has not been able to implement the School Literacy Movement because of their limited facilities, such as the absence of a school library. In addition, the economic background of students' family also affects students' interest in reading. Based on these conditions, literacy activities are focused on basic literacy skills, including reading and writing. Literacy activities are carried out by reading non-academic books for 15 minutes and writing a daily literacy journal. These activities are accompanied by a mentor, a teacher who is appointed by the school. The mentoring activities carried out by English Literature Study Program Community Service team have helped Attin Al Khair Junior High School to start their literacy activities and this program gets positive responses from both teachers and students. Therefore, the literacy activities can be implemented continuously, and become a literacy culture in the school environment.